The potential for involving India in regional production networks: Analyzing vertically specialized trade patterns between India and ASEAN - Meenu Tewari; C. Veeramani; Manjeeta Singh (Indian Council for Research on International Economic Relations (ICRIER), 2015)
At a time when regional production networks have been resurgent, especially in Asia, why has India's integration in regional markets had not been deeper? Using highly disaggregated trade data and an analysis of industry perspectives based on semi-structured interviews with a sample of firms and industry associations relevant to India's trade with ASEAN, the paper found that despite low volumes, vertically specialized trade has been growing between India and ASEAN. Overall, there is significant potential for deepening India's engagement in ASEAN by expanding intermediates exports in the machinery sector, building on its strong performance in the chemicals sector by expanding the export of higher value specialty chemicals, and in general attempting to move up the value chain in the parts, components and assembled goods exported in the road vehicles and transport equipment product categories and telecommunications and sound recording equipment segments where network exports (assembled end products) are important. There is tremendous underexploited potential for growth in electronics and related equipment categories (HS 85). Our field level interviews bore out some of these emerging trends and showed that while East Asia and ASEAN are seen as important destinations for Indian exports, deeper integration is affected by three factors: (i) Indian firms' preoccupation with the large domestic market over exports; (ii) the low value addition in Indian manufacturing which translates into low-value component exports and a high degree of reliance on expensive imports; and (iii) a variety of impediments that add to production costs, such as: sub-optimal scales of production in key intermediate sectors, a near total lack of quality inputs (high quality steel, electronics, quality plastics), precision and high quality tooling, the complete absence of the electronics hardware sector (including semiconductor devices), and a lack of serious R&D or skill development. These structural deficits are compounded by policy costs imposed on firms by the disabling lack of reliable power supply, inadequate infrastructure and logistics, high interest rates and land costs, and an unstable policy environment. Although some firms have found innovative ways to cope, the costs are high. The broader point is that upgrading within regional production networks requires domestic capability formation. (...)
Keywords: F15; F55; F63; O24; O25; 330; Trade policy; regional production networks; vertically specialized trade; task trade; economic upgrading; industrial competitiveness; Asia; India; ASEAN